Acinetobacter baumannii Septicemia in a Recipient of an Allogeneic Hematopoietic Stem Cell Transplantation - Khalid Ahmed Al-Anazi; Baha Abdalhamid; Zeyad Alshibani; Khalid Awad; Abdullah Alzayed; Hoda Hassan; Mohammed Alsayiegh (Case Reports in Transplantation)
Acinetobacter baumannii is a gram-negative, nonfermentative coccobacillus that causes infections in immunocompromised and chronically ill patients and is associated with multidrug resistance. Two days before receiving her nonmyeloablative stem cell allograft, a patient with acute myeloid leukemia developed Acinetobacter baumannii bacteremia that caused septic shock which was successfully treated with imipenem and removal of the central venous catheter. To our knowledge, this is the first report of Acinetobacter baumannii septicemia in a hematopietic stem cell transplantation recipient.